2010
DOI: 10.1007/s10750-010-0305-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nutritional quality of decaying leaf litter in a stream based on fatty acid content

Abstract: We examined the nutritional quality of decaying leaf litter in a third-order forested stream, using measurements of fatty acid (FA) composition over time. We measured changes in concentrations of total, polyunsaturated, microalgal, and microbial marker FAs in mixed-species leaf packs in spring and autumn and effects of including/excluding macroinvertebrates. Initial concentrations of total FAs in litter were significantly less in spring (5.2 mg/g) than in autumn (6.9 mg/g; F = 6.3; P = 0.03), but total FA conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…Differences in the FA composition among aquatic macroinvertebrates, periphyton, and terrestrial leaves suggest that periphyton is the main LC‐PUFA (in particular EPA) source for macroinvertebrates. Although submerged leaves were not available in our study streams in summer and FA of biofilms attached to submerged leaves were not analyzed, previous studies report that submerged leaves as a whole contained no or very little EPA, < 1% (Brett et al ; Torres‐Ruiz and Wehr ; Guo et al c ), which is also confirmed by our leaf FA (Table ). Moreover, seasonal change is unlikely to affect the low‐EPA content of submerged leaves (Torres‐Ruiz and Wehr ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Differences in the FA composition among aquatic macroinvertebrates, periphyton, and terrestrial leaves suggest that periphyton is the main LC‐PUFA (in particular EPA) source for macroinvertebrates. Although submerged leaves were not available in our study streams in summer and FA of biofilms attached to submerged leaves were not analyzed, previous studies report that submerged leaves as a whole contained no or very little EPA, < 1% (Brett et al ; Torres‐Ruiz and Wehr ; Guo et al c ), which is also confirmed by our leaf FA (Table ). Moreover, seasonal change is unlikely to affect the low‐EPA content of submerged leaves (Torres‐Ruiz and Wehr ).…”
Section: Discussionsupporting
confidence: 84%
“…Although submerged leaves were not available in our study streams in summer and FA of biofilms attached to submerged leaves were not analyzed, previous studies report that submerged leaves as a whole contained no or very little EPA, < 1% (Brett et al ; Torres‐Ruiz and Wehr ; Guo et al c ), which is also confirmed by our leaf FA (Table ). Moreover, seasonal change is unlikely to affect the low‐EPA content of submerged leaves (Torres‐Ruiz and Wehr ). Macroinvertebrate primary consumers in our study streams showed limited ability to synthesize EPA from dietary ALA, suggesting they obtained EPA from food sources that are rich in EPA (Brett and Müller‐Navarra ; Wacker et al ; Torres‐Ruiz et al ).…”
Section: Discussionsupporting
confidence: 84%
“…Not only do aquatic insects often emerge with very high abundance and biomass, but they also carry nutrients and essential lipids produced within aquatic environments (Baxter et al 2005;Gratton et al 2008;Gladyshev et al 2009;Torres-Ruiz and Wehr 2010). These aquatic insect subsidies support a multitude of organisms in riparian communities, including arthropods (Collier et al 2002;Burdon et al 2013), birds (Gray 1993;Poulin et al 2010) and bats (Fukui et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that small amounts of labile C exudates released by primary producers can substantially accelerate the decomposition of slow-turnover pools of organic matter (often referred to as recalcitrant organic matter), a process called the ''priming effect'' in both terrestrial (Kuzyakov et al 2000, Fontaine andBarot 2005) and aquatic (Guenet et al 2010, Bianchi 2011 ecosystems. Living primary producers are rich in these essential compounds, and consumption of litter-associated primary producers by detritivores may help meet their nutritional requirements and maintain high detritus-processing activity (Franken et al 2005, Torres-Ruiz andWehr 2010). Under high-nutrient conditions (Fig.…”
Section: Introductionmentioning
confidence: 99%